Ecosystems with the endemic argan tree Sideroxylon spinosum L.: their flora and fauna (Algerian Sahara) - Kechairi, Réda; Benaouf, Zohra; Ould Safi, Mohammed; Megharbi, Ahmed (Biodiversity: Research and Conservation, 2024)
The Tindouf argan groves in the south-western Algerian Sahara, beside Sideroxylon spinosum L. [syn. Argania spinosa (L.) Skeels] have a rich flora and fauna. This study was aimed to assess their species composition. During floristic surveys we recorded 79 plant species, 67 genera, and 31 families. Among them, the Brassicaceae and Fabaceae are the most represented families (12.7% and 11.4% of the flora, respectively), followed by the Asteraceae and Zygophyllaceae (8.9% each). The flora includes 18 rare species (23%) and 16 endemic taxa (20.3%). The Saharo-Sindian element dominates, accounting for 24.1%, compared with 11.4% for the Saharo-Mediterranean and the Mediterranean elements each. The argan tree grows in steppelike plant formations, including pastures, of which 67% are of the desert type. The flora is composed mostly of phanerophytes (19.3%), nanophanerophytes (11.6%), and chamaephytes (35.9%). The argan tree is present in various small facies, along wadi beds, on sandy, rocky, and gravelly substrates. We recorded 25 species of birds, 17 mammals, 9 reptiles, 1 amphibian, and 15 arthropods, mostly insects. Consequently, the remarkable biological richness found within the argan ecosystems of Tindouf in the Algerian Saharan context deserves the attention of international bodies concerned with nature conservation in order to protect it as a biosphere reserve.